2016
DOI: 10.12659/msm.895833
|View full text |Cite
|
Sign up to set email alerts
|

miRNA143 Induces K562 Cell Apoptosis Through Downregulating BCR-ABL

Abstract: BackgroundLeukemia seriously threats human health and life. MicroRNA regulates cell growth, proliferation, apoptosis, and cell cycle. Whether microRNA could be treated as a target for leukemia is still unclear and the mechanism by which microRNA143 regulates K562 cells needs further investigation.Material/MethodsmiRNA143 and its scramble miRNA were synthesized and transfected to K562 cells. MTT assay was used to detect K562 cell proliferation. Flow cytometry and a caspase-3 activity detection kit were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…4a-c), suggesting that S.c-EVs are effective delivery vectors for the tested agents. In a previous study, it's demonstrated that mice receiving an intranasal dose of EV-miR-143 (an apoptosisinducing miRNA as reported previously 5 ) exhibited signi cant inhibition of HeLa tumor growth 25 . We investigated if S.c-EVs could deliver miRNA to tumor tissue and inhibit implanted Hela tumor growth.…”
Section: In Vitro and In Vivo Targeted Delivery Of Therapeutic Agents...mentioning
confidence: 63%
“…4a-c), suggesting that S.c-EVs are effective delivery vectors for the tested agents. In a previous study, it's demonstrated that mice receiving an intranasal dose of EV-miR-143 (an apoptosisinducing miRNA as reported previously 5 ) exhibited signi cant inhibition of HeLa tumor growth 25 . We investigated if S.c-EVs could deliver miRNA to tumor tissue and inhibit implanted Hela tumor growth.…”
Section: In Vitro and In Vivo Targeted Delivery Of Therapeutic Agents...mentioning
confidence: 63%
“…Repression of miR-143 via methylation seems to enhance KMT2A - AFF1 oncogene expression, whereas upregulation of this miRNA could be a therapeutic target for this ALL subgroup [ 141 ]. In the same context, miR-143 overexpression in ALL cells in vitro resulted in growth inhibition and induction of apoptosis by either silencing DNMT3A (DNA methyltransferase 3 alpha) or by downregulating BCR - ABL1 expression in the respective cases [ 142 , 143 ]. A recent study reported significant upregulation of miR-145, which is clustered with miR-143, although this qRT-PCR study included only 13 pediatric ALL cases and 5 controls [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…One group has attempted a novel therapeutic approach based on delivering selected factors in EVs with some promising results. This group engineered EVs to deliver anti-HIV Env antibodies with either an apoptosisinducing miRNA (miR-143) or the chemotherapy compound curcumin, which has been shown to have anti-HIV activity, as well as anti-inflammatory and anti-tumor effects (Liang et al, 2016;Mantzorou et al, 2018;Tan et al, 2019). This group found that they could indeed target Env-expressing cells with exosomes containing the anti-Env antibody and if the exosomes also contained curcumin, the Env-positive cells died (Zou et al, 2019).…”
Section: The Viral Modified Proteinaceous Cargo Of Evs Dictates Novelmentioning
confidence: 99%